A Critical Analysis of Why Female Employees That Are Subjected to Sexual Harassment Do Not Come Out to Report Such Cases - Resty Nazziwa (Uganda Christian University, 2024)
The workplace is meant to be conducive without vices like sexual harassment. Even when employees are sexually harassed, they are expected to come out and make complaints against their employers as different laws, that is to say, Criminal, Civil, International, and regional Instruments all provide for a remedy to the aggrieved employees. However, in reality, despite the existence of laws that protect them against sexual harassment, female employees end up remaining silent and not coming out to make complaints against such employers. This research is hence to be beneficial in a way that it is going to identify different reasons as to why female employees remain silent even when they are sexually harassed and as well come up with recommendations on how to make them speak out. Among the reasons why female employees do not report sexual harassment cases are delays in awarding remedies to the victims that come out to report, the fear of consequences that come with reporting, and the high burden placed on the victim in proving the sexual harassment among others. To overcome this problem, therefore, there is a need for the government through the parliament to amend the Penal Code Act to criminalize sexual harassment. Because Criminal law comes up to punish the convict, with many of them being punished, many female employees will get the guts to come out to report with a view that the convicts will be punished. Female employees who are subjected to sexual harassment should accept that the act is evil and they should in case they have some evidence keep it thoroughly. This will enable them to easily prove such cases and as a result, the employers found guilty will be penalized. This will give guts to many employees to come up and complain in case they are sexually harassed at their places of work as they will have a belief that remedying them will be possible.